Questions of prosecutor supervision in the context of laws in implementing judicial decisions in criminal matters - Sykal, Maksym (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
There are the legal and practical aspects of the implementation of prosecutorial supervision over observance of laws during the execution of judicial decisions in criminal cases are analyzed in the article. The problematic issues of the prosecutor’s supervision over the observance of laws by the penitentiary institutions were revealed. The ways of improvement of the current legislation in the area of activity of the prosecutor’s offices are offered.